Sharia in Africa today : reactions and responses - Chesworth, John.; Kogelmann, Franz. (Islam in Africa, 2014)
Sharīʿa in Africa Today. Reactions and Responses explores how Islamic law has influenced relations between Muslims and Christians, through a series of case studies by young African scholars working in four African countries: in Sudan where total Sharīʿa was applied until recently; in Nigeria where the Northern states re-introduced Sharīʿa courts; in Kenya where the place of Islamic courts has been contested in constitutional debates; in Tanzania where Muslims are calling for the re-introduction of Islamic courts. Each chapter is based on research carried out by the authors, topics include: relations between Muslims and Christians; how Islamic law has impacted on women; new Islamic movements and the state. It is of importance to anyone interested in the impact of Sharīʿa in Africa today.